Discharge planning for children with ventricular septal defect and pulmonary arterial hypertension in China - Xiaoxiao Wu; Qingyin Li; Jingli Chen (Elsevier, 2015)
Objective: To evaluate the effectiveness of discharge planning on maternal caring knowledge, maternal caring behavior, maternal discharge readiness and the rehospitalization of children with ventricular septal defect and pulmonary arterial hypertension (VSD-PAH). Background: Children with congenital heart disease (CHD) with pulmonary arterial hypertension (PAH) have more complications after surgery than those without PAH. Discharge planning is an effective strategy to help children leave the hospital safely, and receive appropriate care after discharge. Methods: A quasi-experimental design was used. Sixty children and their mothers were recruited and divided into two groups: the control group received conventional care, the intervention group received both conventional care and additional discharge planning care. Results: (1) After admission, maternal caring knowledge between the two groups was similar. (2) At discharge, maternal discharge readiness, maternal caring knowledge and maternal caring behavior in the intervention group was significantly higher compared to the control group (t = 3.35, p = 0.001; F = 84.74, p < 0.001; F = 23.82, p < 0.001). This difference persisted after discharge, and was evident at one month and three months after discharge. (3) However, no significant difference in the readmission rate of children after discharge was evident between the two groups. Conclusions: Discharge planning improves the maternal discharge readiness, maternal caring knowledge and maternal caring behaviors. However, this planning did not reduce the readmission rate of children with CHD-PAH.